Feelings first? Sex differences in affective and cognitive processes in emotion recognition. Issue 10 (October 2022) - Bek, Judith; Donahoe, Bronagh; Brady, Nuala
The recognition of emotional expressions is important for social understanding and interaction, but findings on the relationship between emotion recognition, empathy, and theory of mind, as well as sex differences in these relationships, have been inconsistent. This may reflect the relative involvement of affective and cognitive processes at different stages of emotion recognition and in different experimental paradigms. In this study, images of faces were morphed from neutral to full expression of five basic emotions (anger, disgust, fear, happiness, and sadness), which participants were asked to identify as quickly and accurately as possible. Accuracy and response times from healthy males ( n = 46) and females ( n = 43) were analysed in relation to self-reported empathy (Empathy Quotient; EQ) and mentalising/theory of mind (Reading the Mind in the Eyes Test). Females were faster and more accurate than males in recognising dynamic emotions. Linear mixed-effects modelling showed that response times were inversely related to the emotional empathy subscale of the EQ, but this was accounted for by a female advantage on both measures. Accuracy was unrelated to EQ scores but was predicted independently by sex and Eyes Test scores. These findings suggest that rapid processing of dynamic emotional expressions is strongly influenced by sex, which may reflect the greater involvement of affective processes at earlier stages of emotion recognition.